Engineering Micro–Nanomaterials for Biomedical Translation. Issue 9 (30th July 2021) - Chen, Yaping; Alba, Maria; Tieu, Terence; Tong, Ziqiu; Minhas, Rajpreet Singh; Rudd, David; Voelcker, Nicolas H.; Cifuentes-Rius, Anna; Elnathan, Roey
Abstract : Engineered nano–bio interfaces–driven by vertical micro/nanoneedles, nanoparticles, organ‐on‐chip devices, and a diversity of nanosubstrates for mass spectroscopy imaging–are spurring scientific and technological progress, from fundamental to transnational biomedical research. Each class has its own characteristic features, which is critical for their translational uptake, but they broadly share the same range of functionality and applicability at the forefront of modern research and medicine. The review provides insights into unique attributes of microneedle technology and its ability for efficient transdermal transport of therapeutic compounds. The uses of nanoneedle technology in precise manipulation of increasingly complex cellular processes at the cell–material interface and their potential for major improvements for many fundamental research applications and ex vivo cell‐based therapies are highlighted. A snapshot in the use of food and drug administration (FDA)‐approved nanoparticle therapeutics and their applications in nanomedicine is provided. The achievements in organ‐on‐chip technology, particularly at the preclinical stage, and its potential to efficiently screen diverse types of therapeutics are covered. The final section is dedicated to the use of nanomaterial‐enhanced mass spectrometry in drug discovery and imaging. Overall, this review aims to highlight those main rules in the design of bio–nano interfaces that have successfully achieved translation into the market. Abstract : The review discusses the use of engineered nano–bio interfaces–driven by vertical micro/nanoneedles, nanoparticles, organ‐on‐chip devices, and a diversity of nanosubstrates for mass spectroscopy imaging, which are spurring scientific and technological progress from fundamental to transnational biomedical research.